2014
DOI: 10.1002/2014ja020421
|View full text |Cite
|
Sign up to set email alerts
|

Proton acceleration at two‐dimensional dipolarization fronts in the magnetotail

Abstract: Transient reconnection events in the planetary magnetotail give rise to fast plasma jets, whose leading edges are called dipolarization fronts. We perform a test particle simulation of ion acceleration in a 2-D model of dipolarization fronts. We study the dependence of acceleration on several parameters of the model. We obtain that the interaction between the dipolarization front and particles depends on their initial energy h 0 , resulting in a moderate increase of the gained energy with h 0 . The front ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 58 publications
4
36
0
Order By: Relevance
“…Second, as was previously mentioned, observations of ion injections suggest that He ++ ions are accelerated to the energies approximately twice larger than H + and He + ions, whereas in our simulation the difference in acceleration is not as large. Third, similar to previous studies [e.g., Artemyev et al, 2012;Greco et al, 2014], the magnetic perturbation of the front was approximated with a soliton-like quasi-stationary structure propagating earthward relative to global magnetospheric convection. A fully self-consistent model of dipolarization fronts in the inner magnetosphere is required to validate this assumption.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Second, as was previously mentioned, observations of ion injections suggest that He ++ ions are accelerated to the energies approximately twice larger than H + and He + ions, whereas in our simulation the difference in acceleration is not as large. Third, similar to previous studies [e.g., Artemyev et al, 2012;Greco et al, 2014], the magnetic perturbation of the front was approximated with a soliton-like quasi-stationary structure propagating earthward relative to global magnetospheric convection. A fully self-consistent model of dipolarization fronts in the inner magnetosphere is required to validate this assumption.…”
Section: Discussionmentioning
confidence: 85%
“…Second, similar to recent studies [e.g., Artemyev et al, 2012;Greco et al, 2014], we assume that the front propagates radially inward:…”
Section: Empirical Model Of Dipolarization Frontsmentioning
confidence: 91%
“…We consider a two‐dimensional (2‐D) configuration of the DF containing the main magnetic field component B z and two components of the electric field E x , E y which only depend on the coordinates ( x , y ). Furthermore, the DF propagates along the x axis with a constant velocity v ϕ (see schematic view of DF configuration and system geometry in Zhou et al [] and Greco et al []). We introduce dimensionless coordinates ϕ = ( x − v ϕ t )/ L , ψ = y / R , where L is the DF magnetic ramp thickness and R is the DF half width.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…To determine the components of the DF electromagnetic fields, we separate variables ϕ and ψ and solve Maxwell's equations for given b ( ϕ ) function describing the profile of the front magnetic field B z along x axis. In this case, DF magnetic field component takes the form Bz=Bmaxcos(12πψ)b(ϕ), where B max is the amplitude of the DF magnetic field, parameter k = π L /2 R defines the relation between DF scales along x and y axes, and ψ ∈[−1,1] (see Appendix in Greco et al []). The relevant components of DF electric field E = E x e x + E y e y are found from Maxwell equations: [∇× E ] = − ( ∂ B z / ∂ t ) e z and (∇· E ) = 0 (absence of free charges at DF; see discussion in Greco et al []).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…With regard to the geospace environment once more, ion acceleration at dipolarization fronts in the geomagnetic tail has been studied, among others, by Ashour-Abdalla et al (2011), Ukhorskiy et al (2013), Birn and Hesse (2014), Greco et al (2014) and Greco et al (2015). Perri et al (2009) and Greco et al (2010) considered the combined effect of a steady-state dawn-dusk electric field and of stochastic Fermi acceleration due to the presence of transient magnetic structures: by performing a two-dimensional (2-D) test particle simulation, they showed that proton energies of up to 80-100 keV can be reached, in agreement with the above observations.…”
Section: Introductionmentioning
confidence: 99%